Reactive arthritis following Salmonella infection: a population-based study. (May 2013) - Tuompo, R; Hannu, T; Mattila, L; Siitonen, A; Leirisalo-Repo, M
Abstract : Objectives: To study the incidence and clinical picture of Salmonella -associated reactive arthritis (ReA), as well as other reactive musculoskeletal symptoms and the arthritogenicity of various Salmonella enterica ssp . enterica serotypes in the population. Method: We sent a questionnaire on enteric and extraintestinal (especially musculoskeletal) symptoms to 999 consecutive subjects with a Salmonella -positive stool culture. Analysis of self-reported musculoskeletal symptoms was supplemented with a clinical examination of subjects with recent symptoms. Results: Of the 999 Salmonella -positive subjects, 496 (50%) returned the questionnaire. Of these, 4.4% (22/496) had ReA and 13.7% (68/496) had other reactive musculoskeletal symptoms [tendinitis, enthesopathy, or bursitis (ReTe)]. Among the ReA patients, all adults, Salmonella Enteritidis was the most common causative serotype. The clinical picture of patients with ReA was mostly monoarticular or oligoarticular. Human leucocyte antigen (HLA)-B27 was positive in 42% of patients with ReA. The Salmonella O antigens of the 496 subjects belonged to eight groups (B, C, D1, E, G, I, L, and O), all with different major O antigenic determinants. All 22 patients with ReA and all 68 patients with ReTe were in O antigen groups B, C, D1, or E. However, the occurrence of musculoskeletal complications showed no statistically significant difference in relation to different O antigen groups (p = 0.69). Conclusions: ReA occurred in 4.4% of patients after Salmonella infection, with an annual incidence of 1.8/100 000 in Finland. We found no differences in arthritogenicity between different Salmonella serotypes that trigger musculoskeletal complications.